Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) Pada Pembelajaran IPAS di Kelas IV SD Negeri 18 Sungai Nanam Kabupaten Solok (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve student learning outcomes in IPAS learning using the Problem Based Learning (PBL) model in Grade IV of SDN 18 Sungai Nanam, Solok Regency. This type of research is Classroom Action Research (PTK) using qualitative and quantitative approaches. This research was conducted in two cycles, with research procedures consisting of planning, implementation, observation and reflection. Data collection techniques in the form of document analysis, test and non-test techniques. The subjects of this study were teachers and students of grade IV of SDN 18 Sungai Nanam, Solok Regency, totaling 28 students. The results of the study showed that: First, the teaching module of cycle I obtained an average of 83.92% (B), increasing in cycle II to 92.85% (SB). Second, the results of the implementation of learning aspects of teachers in cycle I obtained an average of 80.35% (C), increasing in cycle II to 96.42% (SB). Third, the results of the implementation of learning aspects of students in cycle I obtained an average of 80.35% (B), increasing in cycle II to 96.42% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 75.54% (B), increasing in cycle II to 87.06% (B). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in science learning in grade IV of SDN 18 Sungai Nanam, Solok Regency.